Propuesta de una App móvil para la ruta turística Mancomunada Bosque Seco - Calva Cañar, Leyton Steeven (2023)
Mobile travel applications are a new tool for the promotion and development of tourism in certain destinations, as a result of the tourism adaptation to new information and communication technologies. For the development of the first specific objective, design of the mobile application, information of different attractions included in the Dry Forest Joint Tourist Route was included, taking into account the information of the "Validation Report of the Dry Forest Joint Tourist Route in the Framework of the Updating of the Information of the Strategic Plans of Sustainable Tourism", likewise this information which was included in the mobile application was collected through the summary sheets of the MINTUR. In the second specific objective, which refers to the functional tests, a certain number of people were tested to verify that all the functionalities of the App worked correctly. For the third specific objective, which consists of the promotion plan for the "Dry Forest" Mobile App, we took into account the results obtained from the surveys of the "Validation Report of the Joint Dry Forest Tourism Route in the Framework of the Information Update of the Strategic Plans for Sustainable Tourism", which showed us that the best option to disseminate tourist information about this circuit is through the Internet, through web pages and social networks, 78% of those surveyed stated that the most suitable medium is the aforementioned due to its effectiveness and accessibility. Based on the results of this survey, we proceeded with the creation of the different pages of social networks such as Facebook and Instagram through which the mobile application will be promoted, as well as the information of the Bosque Seco Joint Tourist Route.